2021
DOI: 10.3390/ijms22168535
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanisms of Heat Priming and Thermotolerance in Tobacco Pollen

Abstract: Global warming leads to a progressive rise in environmental temperature. Plants, as sessile organisms, are threatened by these changes; the male gametophyte is extremely sensitive to high temperature and its ability to preserve its physiological status under heat stress is known as acquired thermotolerance. This latter can be achieved by exposing plant to a sub-lethal temperature (priming) or to a progressive increase in temperature. The present research aims to investigate the effects of heat priming on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Another strategy is the application of priming, which consists of a gradual increase in temperature or a brief pre-exposure to a slightly supra-optimal but nonlethal temperature. Mareri et al [7] studied the effects of priming on pollen grain function in tobacco. The results showed that pre-exposure to sub-lethal temperatures (30 • C) positively improves pollen performance by altering its metabolism.…”
Section: Temperature Stressmentioning
confidence: 99%
“…Another strategy is the application of priming, which consists of a gradual increase in temperature or a brief pre-exposure to a slightly supra-optimal but nonlethal temperature. Mareri et al [7] studied the effects of priming on pollen grain function in tobacco. The results showed that pre-exposure to sub-lethal temperatures (30 • C) positively improves pollen performance by altering its metabolism.…”
Section: Temperature Stressmentioning
confidence: 99%
“…Plants, sedentary organisms, are at risk from these changes. The male gametophyte is extremely sensitive to temperature, and its ability to maintain its physiological state under heat stress is known as acquired thermo-tolerance 27 .…”
Section: Assisted Plant Migration: Potential Applicationmentioning
confidence: 99%
“…An important adaptive trait for many land plants is an amazing ability to sense and adapt to changing temperatures (Lamers et al, 2020;Hayes et al, 2021;Mareri et al, 2021;Nishad and Nandi, 2021). Nevertheless, global climate change is predicted to make periods of heat stress increasingly detrimental to plant growth and reproduction (Challinor et al, 2014;Zhao et al, 2017;Cohen et al, 2021;Zandalinas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%